Who Decides and Who Acts? Gender Roles in School-Age Immunization Decisions in Sorong City, Southwest Papua - Nadiyah Kamilia; Sri Riyanti Windesi (Journal of Current Health Sciences, 2026)
School-based immunization in Indonesia (Bulan Imunisasi Anak Sekolah; BIAS) has declined in Sorong City, Southwest Papua, and household pathways behind low uptake remain unclear. This dyadic study compared fathers and mothers of the same child to examine whether gendered roles are reflected in immunization knowledge and decision-making/action. We conducted a cross-sectional survey in two elementary schools and enrolled 151 father–mother pairs through school–primary care coordination. Parents completed a knowledge scale and a 10-item decision-making/action scale covering consent, scheduling, accompaniment, information seeking, and responses to adverse events following immunization. Within-couple differences were tested using paired-samples t tests. Knowledge did not differ between fathers and mothers (mean difference = −1.58, SD = 27.57; t(150) = −0.70, p = .483; Cohen’s dz ≈ −0.06). Decision-making/action differed markedly, with fathers scoring lower than mothers (mean difference = −38.46, SD = 18.07; t(150) = −26.16, p < .001; Cohen’s dz ≈ −2.13). Mothers scored higher on 9 of 10 items, while fathers more often endorsed refusal when side effects occur. Barriers therefore cluster in decision authority and task execution rather than information deficits. BIAS should strengthen couple-oriented consent and deliver father-targeted risk communication on expected reactions and care-seeking, and align school messages for both parents. Abstrak. Imunisasi berbasis sekolah di Indonesia (Bulan Imunisasi Anak Sekolah; BIAS) mengalami penurunan di Kota Sorong, Papua Barat Daya, dan jalur rumah tangga yang mendasari rendahnya cakupan masih belum jelas. Studi dyadik ini membandingkan ayah dan ibu dari anak yang sama untuk menilai apakah peran berbasis gender tercermin pada pengetahuan imunisasi serta pengambilan keputusan/tindakan. Survei potong lintang dilakukan di dua sekolah dasar dan melibatkan 151 pasangan ayah–ibu melalui koordinasi sekolah dengan layanan kesehatan primer. Orang tua mengisi skala pengetahuan dan skala pengambilan keputusan/tindakan berisi 10 butir yang mencakup persetujuan, penjadwalan, pendampingan, pencarian informasi, serta respons terhadap kejadian ikutan pascaimunisasi. Perbedaan dalam pasangan diuji menggunakan uji t berpasangan. Pengetahuan tidak berbeda antara ayah dan ibu (selisih rerata = −1,58, SD = 27,57; t(150) = −0,70, p = 0,483; Cohen’s dz ≈ −0,06). Sebaliknya, pengambilan keputusan/tindakan berbeda secara bermakna, dengan skor ayah lebih rendah dibanding ibu (selisih rerata = −38,46, SD = 18,07; t(150) = −26,16, p < 0,001; Cohen’s dz ≈ −2,13). Ibu memiliki skor lebih tinggi pada 9 dari 10 butir, sedangkan ayah lebih sering menyatakan kecenderungan menolak bila ada efek samping. Dengan demikian, hambatan lebih terkonsentrasi pada otoritas keputusan dan pelaksanaan tugas daripada defisit informasi. Program BIAS perlu memperkuat persetujuan yang mendorong diskusi pasangan, komunikasi risiko yang menarget ayah tentang reaksi yang diharapkan dan langkah mencari layanan, serta penyelarasan pesan sekolah kepada kedua orang tua.